Electrical machines based DC/AC energy conversion schemes for the improvement of power quality and resiliency in renewable energy microgrids. (September 2017) - V. Pavan Kumar, Y.; Bhimasingu, Ravikumar
Highlights: DC/AC energy conversion schemes based on the theory of DC Motor and DFIG. Mimics the behavior of electric machines based power conversion in microgrids. Injects virtual moment of inertia into the microgrid's operation. Improves power quality and resiliency through the smooth control of P, Q, V and f . Adheres IEEE-1547 regulations for healthy interaction with utility grid. Abstract: The power quality and resiliency (or self-healing capacity) characteristics of a renewable energy based microgrid (REM) are limited majorly due to their inherent dependency on the static power electronics based energy conversion devices. Whereas, conventional electrical machines based power plants possess good power quality and resiliency characteristics due to their high inertia and control features. So, the REMs' research need to be shifted towards making its operation similar to conventional electrical machines based power plant. With this intent, this paper proposes two DC/AC energy conversion schemes that are designed based on the theory of electrical machines such as DC Motor (DCM) and Doubly Fed Induction Generator (DFIG). The first scheme is a rotary inverter (named as RDCMIGI) that replaces the conventional static power electronic inverter with a real DCM-DFIG set. The second scheme is a static inverter (named as VDCMIGI) that uses a pulse width modulated power electronic inverter, whose modulating signals are generated through a closed loop virtual DCM-DFIG based control system. These two schemes emulate the behavior of electrical machines based conventional power plant in REM, which leads to the improvement of power quality through the smooth control of voltage/frequency and resiliency through the injection of necessary moment of inertia. For the analysis, the conventional/proposed energy conversion schemes are modeled in MATLAB/Simulink® and are tested during various uncertainties. From the results, it is observed that the proposed DC/AC energy conversion schemes have effectively improved the power quality and resiliency, and thereby, leverages REMs as better future grids.